Wheat straw- and maize straw-derived biochar effects on the soil cadmium fractions and bioaccumulation in the wheat–maize rotation system - Dun, Yu; Wu, Chao; Zhou, Ming; Tian, Xia; Wu, Guoqing (Frontiers in Environmental Science, 2022)
Wheat-maize rotation is one of the most popular system and successful intensification cropping systems in the Northern China while soils in some of this area are contaminated by cadmium (Cd). However, few studies have performed experiments on the reduction of Cd accumulation in the wheat-maize rotation system. In this study, wheat- and maize-derived biochars are applied to the Cd-contaminated soil to reduce the Cd accumulation in the wheat and maize plants. The results showed soil biochar applications can significantly decrease DTPA-extracted Cd concentrations by 12.7-26.0% and 13.1-20.5% by wheat- and maize-derived biochars, respectively. Sequential extractions showed that biochar applications significantly reduced the Cd mobility and bioavailability in soils and changed the exchangeable and carbonate-bound fractions of Cd to organic material-bound and residual fractions. The biochar applications increased the plant growth, yield and quality of both wheat and maize, especially significant increase in the high dosages. The biochar applications also improved the antioxidant enzyme activities and reduce the reduction of MDA in both wheat and maize roots. The Cd concentrations in the wheat grains were reduced by 38.1-91.5% and 65.9-80% and maize grain Cd concentrations were reduce by 20.9-54.2% and 30.8-44% by wheat- and maize-derived biochar applications, respectively and the Cd concentrations in the root, stem, and leaf were also significantly reduced. The wheat-derived biochar was more effectively on the Cd reduction in soil bioavailable fractions and Cd accumulation in crop plants.